Perancangan Video Klip Profil Komunitas K-Pop Dance Invasion DC Jakarta dengan Teknik Camera Movement - Martinus Eko Prasetyo; Zevri Zevri; Shierly Everlin (Institut Seni Indonesia Yogyakarta, 2022)
The development of Korean culture in many countries, including Indonesia in recent years, has had an impact on most of the mass media in Indonesia displaying various Korean nuances such as musical performances, dramas, and films. Moreover, the Indonesian people are also familiar with and use products originating from Korea. K-pop, also known as Korean pop music, has the ability to penetrate national borders and is popular overseas. K-pop also managed to enter the American charts, Billboard which is the standard to measure the quality of the global music industry. The spread of K-pop in Indonesia has also made many Korean artists visit and hold concerts in Indonesia.This writing provides information about the facts of taking videography. This study uses qualitative methods to collect accurate data and information as a guide in designing Profie's video clips. The results of this study will explain the design of the Profile video clip of the largest K-Pop dance cover community in Indonesia, namely Invasion DC. Based on information data about Invasion DC, how the development of this community when it was first established until it became now, and the characteristics of Invasion DC itself. This design is expected to provide information and an overview of the DC Invasion community in making Profile video clips with the Camera Movement technique.The development of Korean culture in many countries, including Indonesia in recent years, has had an impact on most of the mass media in Indonesia displaying various Korean nuances such as musical performances, dramas, and films. Moreover, the Indonesian people are also familiar with and use products originating from Korea. K-pop, also known as Korean pop music, has the ability to penetrate national borders and is popular overseas. K-pop also managed to enter the American charts, Billboard which is the standard to measure the quality of the global music industry. The spread of K-pop in Indonesia has also made many Korean artists visit and hold concerts in Indonesia.This writing provides information about the facts of taking videography. This study uses qualitative methods to collect accurate data and information as a guide in designing Profie's video clips. The results of this study will explain the design of the Profile video clip of the largest K-Pop dance cover community in Indonesia, namely Invasion DC. Based on information data about Invasion DC, how the development of this community when it was first established until it became now, and the characteristics of Invasion DC itself. This design is expected to provide information and an overview of the DC Invasion community in making Profile video clips with the Camera Movement technique.